2016
DOI: 10.1016/j.micres.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Significance of hyphae formation in virulence of Candida tropicalis and transcriptomic analysis of hyphal cells

Abstract: Recently, the proportion of Candida tropicalis in clinical isolates has significantly increased. Some C. tropicalis strains colonize the skin or mucosal surfaces as commensals; others trigger invasive infection. To date, the pathogenicity of C. tropicalis has not been thoroughly researched. This study reports several virulence factors, including biofilm and hyphae formation, proteinase, phospholipase, lipase and hemolytic activity, in 52 clinical isolates of C. tropicalis collected from five hospitals in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, other authors later reported phospholipase activity in isolates of this species. A recent study conducted by Jiang et al ( 2016 ) with 52 strains of C. tropicalis found phospholipase activity in 31 isolates from different clinical sources. However, strains showed low enzyme production.…”
Section: Virulence Factorsmentioning
confidence: 96%
“…However, other authors later reported phospholipase activity in isolates of this species. A recent study conducted by Jiang et al ( 2016 ) with 52 strains of C. tropicalis found phospholipase activity in 31 isolates from different clinical sources. However, strains showed low enzyme production.…”
Section: Virulence Factorsmentioning
confidence: 96%
“…Under certain conditions, these yeast cells experience a special morphological alteration and turn into elongated cells called hyphae. It has been shown that such a conversion is a fundamental feature of the pathophysiology and the virulence of these strains [13,14]. As a matter of fact, opportunistic pathogens commensally colonize the skin or mucosal surfaces of the gastrointestinal and urogenital tracts mostly in yeast form, then yeasts switch to virulent hyphae which can disseminate internal organs or cause mucocutaneous infections [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Candida genus is comprised of about 150 species of yeast-like fungi. In general, they are classified as asexual diploid fungi that can exist in the form of yeasts or hyphae [5]. Candida species such as C. albicans, C. tropicalis, C. krusei, C. lusitaniae, C. dubliniensis, C. kefyr, C. guilliermondii, C. parapsilosis and C. lipolytica are present in the oral cavity as commensal microorganisms and these can act as opportunistic pathogens in cases of low immune system [6].…”
Section: Introductionmentioning
confidence: 99%